Health information literacy as an increasingly important component of health literacy - Niedźwiedzka, Barbara (Polish Journal of Public Health, 2013)
The paper presents  briefly the evolution and meaning of the term “health  literacy” and the growing role of in- formation literacy among health competencies. The grow- ing importance of the latter for the level of citizens’ health literacy is a consequence of the information revolution, and is associated with increasing self-reliance of people in gaining information about health and disease, increasingly beyond the control of medical professionals and in aggres- sive informational environment. A high level of informa- tion literacy, according to the author, may protect against health hazards arising from use of inappropriate or incorrect information, and therefore building health information skills should  become an integral part of any health education.